How does screen time affect language development? - Serratrice, Ludovica (Babylonia (Asssociation Babylonia Suisse), 2024)
Between September and December 2023, Babylonia collected questions from parents regarding their children's language development. This article aims to answer the following questions: I am the mom of a 17 months old. My husband lets him watch some TV (mainly kids songs, in German, my husband’s first language) but I don’t because I heard that it is bad for his language development. I recently noticed that our son actually learns things from those videos (especially counting on his fingers, or clapping when instructed etc.) I don’t know what to think anymore: is educational TV really that bad for language learning in toddlers? What are the effects of screen time on language development? Can the child learn the English language by watching English-speaking cartoons? [Summary generated by GPT-4o - we refer the reader to the article in English in PDF format for a complete answer] The article explores the effects of screen time on language development in young children, addressing parents' concerns. While prolonged exposure to screens and background television is associated with weaker language skills, age-appropriate educational programs, especially when viewed with an adult, can have positive effects on language acquisition. When an adult co-watches with a child, it creates interaction opportunities that are crucial for language development. Adults can ask open-ended questions (e.g., "Why is the penguin sad?"), check the child's understanding, introduce new words, and encourage the child to actively participate in the conversation. This type of interaction is essential because language learning relies on exchange and interaction rather than passive exposure. Educational programs, like "Dora the Explorer," stand out for their educational goals: they introduce new words and concepts through repetition and diverse contexts. However, even these programs cannot replace rich human interactions that promote deep learning. Watching videos or cartoons in a foreign language, like English, may allow children to learn a few isolated words, but this is not sufficient for meaningful learning without real interactions with native speakers or other sources of interactive exposure. Furthermore, the article emphasizes that different types of media (written texts, illustrated books, videos) can support different skills, such as the ability to make inferences. This skill, essential for reading comprehension, can be facilitated by audiovisual media through the combination of visual, auditory, and linguistic cues. In conclusion, screen time is not fundamentally bad for language development. What matters is the content being watched, how it is used, and especially the presence of an adult to encourage interaction and active learning. Screens can be a useful tool, but they do not replace the richness of human exchanges in developing language skills.